Dementia Lab 2019 : making design work : engaging with dementia in context : 4th Conference, D-Lab 2019, Eindhoven, The Netherlands, October 21-22, 2019, Proceedings /: making design work : engaging with dementia in context : 4th Conference, D-Lab 2019, Eindhoven, The Netherlands, October 21-22, 2019, Proceedings. (2019) - Unknown
No abstract available